2019
DOI: 10.1175/jhm-d-18-0155.1
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Extreme Precipitation in the Northeast United States: 1979–2014

Abstract: Extreme precipitation can have significant adverse impacts on infrastructure and property, human health, and local economies. This paper examines recent changes in extreme precipitation in the northeast United States. Daily station data from 58 stations missing less than 5% of days for the years 1979–2014 from the U.S. Historical Climatology Network were used to analyze extreme precipitation, defined as the top 1% of days with precipitation. A statistically significant (95% confidence level) increasing trend o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(60 citation statements)
references
References 22 publications
4
45
0
Order By: Relevance
“…Unsolved issues remain and should be further explored. First, ARs in the warm seasons reported in this study were likely associated with the extratropical cyclones moving eastward from the west and the tropical cyclones moving poleward along the North American east coast (Howarth et al 2019). ARs could be associated with only one type of cyclone or induced when both types of cyclones appeared simultaneously and interacted through a tropical-extratropical coupling.…”
Section: Summary and Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Unsolved issues remain and should be further explored. First, ARs in the warm seasons reported in this study were likely associated with the extratropical cyclones moving eastward from the west and the tropical cyclones moving poleward along the North American east coast (Howarth et al 2019). ARs could be associated with only one type of cyclone or induced when both types of cyclones appeared simultaneously and interacted through a tropical-extratropical coupling.…”
Section: Summary and Discussionmentioning
confidence: 72%
“…By contrast, to the best of our knowledge, the AR activity along the North American northeast coast (NANC) has not been systematically explored despite the fact that the increased precipitation trend since 1979 has been documented in several studies (Griffiths and Bradley 2007;Brown et al 2010;Walsh et al 2014;Frei et al 2015;Huang et al 2017). A recent study by Howarth et al (2019) on extreme precipitation in the northeastern United States reported an increasing trend in the frequency of rainfall events exceeding 50 mm in spring, summer, and autumn, with the most robust trend observed in autumn. They further identified 24 extreme events that exceeded 150 mm, finding that all of those events occurred in summer and autumn.…”
Section: Introductionmentioning
confidence: 99%
“…A wide scope of studies related to changes in precipitation and other climatic factors affecting soil moisture levels in the Mid-Atlantic region have been successfully conducted and provide context for this work. That research has found the region has been experiencing higher average annual amounts of rainfall and frozen precipitation due to a wetter climate, as defined in the meteorological context (Howarth et al 2019). The magnitude of this increase depends on the period of study, selection of states, utilized datasets, and time series data methodology, but relatively large trends have been recorded.…”
Section: Scopementioning
confidence: 99%
“…The managers then combined this broad-scale information with their knowledge of the local landscape to identify attributes of the property that they believed would increase or decrease the risks from climate change. For example, extreme rain events are becoming more frequent and severe as a result of climate change [49]; many extreme rain and storm events have damaged recreational resources in the GMNF in recent years [50] and these types of events are expected to continue increasing [51,52]. Many of the winter recreational activities that GMNF visitors value are vulnerable to warmer temperatures and shorter winter seasons, and changes in seasonality are generally expected to change recreational uses and patterns toward warm-season activities [1,6].…”
Section: Step 2: Site-specific Climate Change Impacts and Vulnerabilimentioning
confidence: 99%